Digital Marketing and Financial Reporting Training for Cahaya MSMEs in Meddelan Lenteng Village, Sumenep - Hardiansyah, Ivo Tayyib; Firmawan, Riqi; Riskiyah, Khofifah Mamluatur; Putri, Dwita Hartika; Ladesrah, Desy; Anwarillah, M Varel; Yandari, Aprilya Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to develop a strategy to increase sales using digital marketing and financial reporting training so that light MSMEs will increase in the future. By using a qualitative approach method. The results of this research show that digital marketing assistance through the use of social media (Shopee, Instagram, Tik-tok, Facebook) can strengthen marketing aspects for Cahaya MSMEs while still implementing the 4P strategy (product, price, promotion, place). Meanwhile, financial reporting training can contribute to improving the financial management of Cahaya MSMEs. Such as the implementation stages in this research, namely, the preparation stage by the group, carrying out the first visit, determining the title and solving the problem, submitting the article title, carrying out the second visit